Description of a new species of the genus Halpe Moore, 1878 from Hainan, China (Hesperiidae, Hesperiinae) - Xue, Guo-Xi; Lo, Yik Fui Philip; Inayoshi, Yutaka; Li, Jia-Ling; Li, Meng (Zootaxa, 2026)
A new species, namely Halpe hainanensis sp. nov., is described from Hainan, China based on two male specimens. Judging from the wing patterns, the new species is slightly different from H. gamma Evans, 1937, H. interposita Devyatkin, 2008 and H. hsuyufengi Xue & Li, 2025, but it can hardly be distinguished from H. gammoides Devyatkin, 2008 and H. inayoshii Xue & Li, 2025. However, the male genitalia of the new species obviously differ from those of the five congeners. A molecular analysis based on the 658 bp COI gene sequences supports the validity of the new species.